Analysis of the Effectiveness of the Healthy School Program on Changes in Students’ Clean and Healthy Living Behaviors at Junior High School - Ngurah Mahendra Dinatha (PROMOTOR, 2026)
The Healthy School Program is a strategic government initiative aimed at creating an educational environment that supports the implementation of Clean and Healthy Living Behavior (CHLB) among students. However, the program’s effectiveness in changing students’ behavior still requires further investigation. This study aims to analyze the effectiveness of the Healthy School Program on changes in CHLB among students at SMPN 5 Bajawa. A quantitative approach with a descriptive-analytical method was used. The research sample consisted of 171 students selected through proportionate stratified random sampling. Data were collected through questionnaires, observations, interviews, and documentation, and then analyzed using validity and reliability tests, normality tests, Pearson correlation tests, and simple linear regression analysis. The results showed that the implementation of the Healthy School Program was categorized as good (M = 4.10), and students’ CHLB behavior was also in the good category (M = 4.05). The correlation value of 0.692 with a significance level of 0.000 indicates a positive and significant relationship between program effectiveness and students’ CHLB behavior. Regression analysis revealed that the program’s effectiveness contributed 47.9% to changes in students’ behavior, while the remaining percentage was influenced by factors outside the school environment. Therefore, the Healthy School Program has proven effective in improving students’ clean and healthy living behaviors, although aspects related to healthy food consumption still need to be strengthened through educational, collaborative, and sustainable activities involving schools, families, and health institutions.